Stress testing and asset allocation for pension fund - Pinto, José Florêncio Ferreira (2017)
Stress testing is a useful and increasingly popular method of analysing the resilience of financial systems to adverse events. It has been introduced recently to the pensions sector, in some countries, as well. This dissertation aim is to present results from a stress testing based on three different scenarios, two of them with adverse financial market scenarios and the last one related with longevity. The main goals of this test are to observe the impact of the shocks applied to the prime financial assets available in the financial market and to understand their significance in the pension fund portfolio.